2019
DOI: 10.1001/jamaoto.2019.1987
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Autofluorescence Parathyroid Identification in Patients With Multiple Endocrine Neoplasia Type 1

Abstract: infrared (NIR) autofluorescence of the parathyroid gland enables intraoperative gland identification without the need for contrast agent injection. However, whether real-time autofluorescence imaging is useful in patients with multiple endocrine neoplasia type 1 (MEN1) and primary hyperparathyroidism is unknown.OBJECTIVE To compare quantified intraoperative parathyroid autofluorescence imaging results for patients with MEN1-associated vs those with non-MEN1 sporadic primary hyperparathyroidism. DESIGN, SETTING… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…It would not be a classic "re-operation" at that time given that all parathyroid gland(s) would be removed in any explored quadrant at the time of the primary operation 68 . Of note, in a small study, autofluorescence does not appear to be a useful adjunct during surgery in these patients 69 .…”
Section: Long-term Outcomesmentioning
confidence: 79%
“…It would not be a classic "re-operation" at that time given that all parathyroid gland(s) would be removed in any explored quadrant at the time of the primary operation 68 . Of note, in a small study, autofluorescence does not appear to be a useful adjunct during surgery in these patients 69 .…”
Section: Long-term Outcomesmentioning
confidence: 79%
“…A possible reason for this is their final histology. In Reference 36, the impact of hyperthyroidism on the detection of the parathyroid using NIR autofluorescence was evaluated. It was shown that the pathology decreases the parathyroid gland's autofluorescence and increases the autofluorescence of the surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with secondary hyperparathyroidism, the down-regulation of calcium-sensing receptors leads to a decrease in fluorescence intensity compared to that of normal PGs (23). In addition, Squires et al noted significantly lower quantified absolute values of parathyroid AF in situ and ex vivo and significantly lower parathyroidto-background AF ratios for patients with vs. without multiple endocrine neoplasia type 1 (MEN1) (24).…”
Section: Wwwbiosciencetrendscommentioning
confidence: 99%